(untitled) - Scheick, John T. (New York, 1997)
The book presents the core topics of linear algebra that are essential to its use in contemporary mathematics, applied mathematics, engineering, and the sciences. Also, in an effort to illustrate the applicability of this core material, many applications are woven into the text in a wide variety of settings
Keywords: Algebra, linear